POVERTY AND THE FORCES OF CHANGE IN AFRICA - Awoniyi, S. (European Scientific Journal, ESJ, 2013)
The aim of this work is to examine poverty and the forces of change in Africa in order to investigate the precarious socioeconomic situation that designates several events from the internal influences and the western network society. The socioeconomic and political interactions of the highly industrialized capitalist countries and the implications of such interactions on other developing nations in the global system are hereby discussed. The paper posits that the intrinsic forces against the resolution towards meaningful development of the Africa in the midst of abundant human and natural resources are not rightly directed. However, the assistance proclaimed by the western world is in turn based on selfishness and exploitation. Recommendations are proffered to enhance attitudinal re-orientation towards the development of the people of Africa as in other climes. A socio-ethical approach was utilized in the data analysis.